Taxonomic implications of describing a new species of Loimia (Annelida, Terebellidae) with two size-dependent morphotypes - Martin, Daniel; Capa, Maria; Martínez, Alejandro; Costa, Ana Cristina (European Journal of Taxonomy, 2022)
We describe Loimia davidi sp. nov. (Annelida, Terebellidae) from São Miguel Island (Azores). It resembles Loimia gigantea (Montagu, 1819) (English Channel) in having very large adults, the ventral shield shape and the types of capillary notochaetae (three), while differing in shape and colour of the lateral lappets, branchiae length, the arrangement of segments, ventral shields, uncini and pygidial papillae. Large (> 30 cm long) and small (≈ 5 cm long) specimens of L. davidi sp. nov. show typically interspecific morphological differences while clustering in a single entity after species delimitation analyses of a cytochrome c oxidase I fragment. Therefore, we consider them to belong to a single species and discuss the taxonomic implications of size-dependent morphological differences. Within Loimia, we (1) suggest that large specimens may have been scarcely reported due to their rarity and collecting difficulty, while small specimens may have been reported either as ‘sp.’ or as the ‘cosmopolitan’ Loimia medusa (Savigny, 1822), (2) evaluate the size-related morphological disparity in all described species using a hypervolume analysis, (3) identify possible similar size-dependency in previously described species, (4) summarise the morphological information of all known species of Loimia; and (5) discuss on the four species reported in Europe.